Effect of cryoprotectants on the reconstitution of silica nanoparticles produced by sol-gel technology - Andreani, Tatiana; Kiill, Charlene Priscila [UNESP]; Souza, Ana Luiza R. de [UNESP]; Fangueiro, Joana F.; Doktorovova, Slavomira; Garcia, Maria L.; Gramiao, Maria Palmira Daflon [UNESP]; Silva, Amelia M.; Souto, Eliana B. (Springer, 2015)
Freeze-drying has widely been applied to improve the stabilization of colloidal drug carriers. In the present study, the effect of cryoprotectants on the physicochemical characteristics of silica nanoparticles (SiNP) during the freeze-drying process has been extensively investigated. SiNP were synthesized by sol-gel technology and freeze-dried in the presence of sorbitol, trehalose, and/or mannitol at different concentrations and ratios. Dynamic light scattering (DLS), atomic force microscopy (AFM), X-ray diffraction analysis (XRD), and differential scanning calorimetry (DSC) have been used for particle characterization after freeze-drying. Based on the obtained results, SiNP in the presence of mannitol showed a more crystalline behavior in comparison to nanoparticles with sorbitol or trehalose (confirmed by DSC and XRD). SiNP in the presence of trehalose showed a more crystalline structure than SiNP in the presence of sorbitol. However, trehalose was more efficient in preserving the particle size of nanoparticles during the freeze-drying process. The optimal concentration of trehalose for preserving silica nanoparticles was 10 % at a ratio of (1:1). During the freeze-drying process, trehalose is able to replace water molecules due to the strong interaction via hydrogen bounds between silanol groups present in SiNP surface and the sugar, forming a stable layer around the particle and thus preserving the particle physical properties.
Keywords: Silica nanoparticles; Sol-gel; Freeze-drying; Stability; Cryoprotectants